Hardware/software co-design for real time embedded image processing: A case study - Pedre, S. (2012)
Many image processing applications need real time performance, while having restrictions of size, weight and power consumption. These include a wide range of embedded systems from remote sensing applications to mobile phones. FPGA-based solutions are common for these applications, their main drawback being long development time. In this work a co-design methodology for processor-centric embedded systems with hardware acceleration using FPGAs is applied to an image processing method for localization of multiple robots. The goal of the methodology is to achieve a real-time embedded solution using hardware acceleration, but with development time similar to software projects. The final embedded co-designed solution processes 1600×1200 pixel images at a rate of 25 fps, achieving a 12.6× acceleration from the original software solution. This solution runs with a comparable speed as up-to-date PC-based systems, and it is smaller, cheaper and demands less power. © 2012 Springer-Verlag.